Analisis laporan arus kas daerah dalam Manilai Fundamental Fiskal - Tariza Tariza; A. Dahri AP; Sultan Sultan (LPPM Sekolah Tinggi Ilmu Ekonomi Al-Washliyah Sibolga, 2023)
This study aims to determine regional fiscal fundamentals by analyzing the cash flow reports of the Luwu Regency Government for the 2017-2021 fiscal year. The research method used is the method of data description and exposition. The description method is used to describe the cash flow of Luwu Regency government activities, while the exposition method is used to analyze cash flow reports for the 2017-2021 fiscal year. The data collection technique uses literature study, namely secondary data in the form of financial reports for the 2017-2021 fiscal year. The results showed that the net cash flow of operating activities had a positive balance, as well as the net cash flow of investing activities and net cash flow of financing activities with a negative balance. This indicated that the Fiscal Fundamentals of the Luwu Regency government had good cash financial performance.